FROM THE HISTORY OF TWO FAILED TRADE DYNASTIES OF KHASAVYURT AND GROZNENSKY DISTRICTS OF THE TERSK REGION (end of the XIX - XX centuries) - Gusejnov, G -RA-K (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with the history of two generations of merchant families of the Guseinovsand the Mirzoevsfrom Khasavurt and Grozny districts of Terskyarea of the Russian Empirethat intermarried before the First World War. The author traces the change of their social status from the times of the Caucasian war to the Soviet period.